A Disrupted Historical Fire Regime in Central British Columbia - Brookes, Wesley; Daniels, Lori D.; Copes-Gerbitz, Kelsey; Baron, Jennifer N.; Carroll, Allan L. (Frontiers in Ecology and Evolution, 2021)
In the 2017 and 2018, 2.5 million hectares burned across British Columbia, Canada, including unanticipated large and high-severity fires in many dry forests. To transform forest and fire management to achieve resilience to future megafires requires improved understanding historical fire frequency, severity and spatial patterns. Our dendroecological reconstructions of 35 plots in a 98-hectare study area in a dry Douglas-fir forest revealed historical fires that burned at a wide range of frequencies and severities at both the plot- and study-area scales. The 23 fires between 1619 and 1943 burned at intervals of 10‒30 years, primarily at low- to moderate-severity that scarred trees but generated few cohorts. In contrast, current fire-free intervals of 70‒180 years exceed historical maximum intervals. Of the six widespread fires from 1790‒1905, the 1863 fire affected 86% of plots and was moderate in severity with patches of higher severity that generated cohorts at fine scales only. These results indicate the severity of fires varied at fine spatial scales, and offer little support for the common assertion that periodic, high-severity, stand-initiating events were a component of the mixed-severity fire regime in these forest types. Many studies consider fires in the late 1800s relatively severe because they generated new cohorts of trees, and thus, emphasize the importance of high-severity fires in a mixed-severity fire regime. In our study area, the most widespread and severe fire was not a stand-initiating fire. Rather, the post-1863 cohorts persisted due disruption of the fire regime in the 20th century when land-use shifted from Indigenous fire stewardship and early European settler fires to fire exclusion and suppression. In absence of low-to-moderate severity fires, contemporary forests are dense with closed canopies that are vulnerable to high-severity fire. Future management should reduce forest densities and to restore stand- and landscape-level heterogeneity and increase forest resilience. The timing and size of repeat treatments such as thinning of subcanopy trees and prescribed burning, including Indigenous fire stewardship, can be guided by our refined understanding of the mixed-severity fire regime that was historically dominated by low-to-moderate-severity fires in this dry forest ecosystem.